Estrogens sensitize anterior pituitary gland to apoptosis - Pisera, Daniel Alberto (2004)
Tissue homeostasis results from a balance between cell proliferation and cell death by apoptosis. Estradiol affects proliferation as well as apoptosis in hormone-dependent tissues. In the present study, we investigated the apoptotic response of the anterior pituitary gland to lipopolysaccharide (LPS) in cycling female rats, and the influence of estradiol in this response in ovariectomized (OVX) rats. The OVX rats were chronically estrogenized with implanted Silastic capsules containing 1 mg of 17beta-estradiol (E2). Cycling or OVX and E2-treated rats were injected with LPS (250 microg/rat ip). Apoptosis was determined by the terminal deoxynucleotidyl-mediated dUTP nick-end labeling (TUNEL) method in sections of the anterior pituitary gland and spleen. Chronic estrogenization induced apoptosis in the anterior pituitary gland. Acute endotoxemia triggered apoptosis of cells in the anterior pituitary gland of E2-treated rats but not of OVX rats. No differences were observed in the apoptotic response to LPS in spleen between OVX and E2-treated rats. The apoptotic response of the anterior pituitary to LPS was variable along the estrous cycle, being higher at proestrus than at estrus or diestrus I. Approximately 75% of the apoptotic cells were identified as lactotropes by immunofluorescence. In conclusion, our results indicate that estradiol induces apoptosis and enables the proapoptotic action of LPS in the anterior pituitary gland. Also, our study suggests that estrogens may be involved in anterior pituitary cell renewal during the estrous cycle, sensitizing lactotropes to proapoptotic stimuli.